Implicating Causal Brain Magnetic Resonance Imaging in Glaucoma Using Mendelian Randomization - Liu, Kangcheng; Wu, Pengfei; Chen, Bolin; Cai, Yingjun; Yuan, Ruolan; Zou, Jing (Frontiers in Medicine, 2022)
Background: Glaucoma is hypothesized to originate in the brain but manifests as an eye disease as it possesses the common features of neurodegeneration diseases. But there is no evidence to demonstrate the primary brain changes in glaucoma patients. In the present study, we have used Mendelian randomization (MR) to understand the causal effect of brain alterations on glaucoma. Methods: Our MR study was carried out using summary statistics from genome-wide associations for 110 diffusion tensor imaging (DTI) measurements of white matter (WM) tracts (17,706 individuals), 101 brain region-of-interest (ROI) volumes (19,629 individuals), and glaucoma (8,591 cases, 210,201 control subjects). The causal relationship was evaluated by multiplicative random effects inverse variance weighted (IVW) method and verified by two other MR methods, including MR Egger, weighted median, and extensive sensitivity analyses. Results: Genetic liability to fornix fractional anisotropy (FX.FA) (OR=0.71, 95%CI=0.56-0.88, P=2.44×10-3), and uncinate fasciculus UNC.FA (OR=0.65, 95%CI=0.48-0.88, P=5.57×10-3) was associated with a low risk of glaucoma. Besides, the right ventral diencephalon (OR=1.72, 95%CI=1.17-2.52, P=5.64×10-3) and brain stem (OR=1.35, 95%CI=1.08-1.69, P=8.94×10-3) were associated with the increased risk of glaucoma. No heterogeneity and pleiotropy were detected. Conclusions: Our study suggests that the fornix and uncinate fasciculus degenerations and injures of the right ventral diencephalon and brain stem potentially increase the occurrence of glaucoma and reveal the existence of the brain-eye axis.